Safeguarding the provision of public services in rural border areas: A case study of the Greater Region - Kirsten Mangels; Julia Wohland (Border Futures - Zukunft Grenze - Avenir Frontière: The future viability of cross-border cooperation, 2022)
In the context of demographic change and the associated shrinking and aging of the population, the safeguarding of public services in rural areas faces great challenges. Rural border areas find themselves in a unique situation due to their location, and must overcome additional challenges if they want to cooperate with their neighbours in the provision of public services. This paper examines cross-border cooperation in public service provision in rural areas of the Greater Region. The area examined here comprises the German territorial authorities on the German-French border within the Greater Region. An analysis of the responsibilities for and understanding of public services in Germany and France, a concise inventory of education and healthcare services, a written survey of German territorial authorities in the German-French border area, and case studies of projects (e.g. INTERREG A projects) are used to demonstrate the successes, problems and opportunities of cross-border approaches.
urn:nbn:de:0156-40971511; hdl:10419/258994; https://econpapers.repec.org/RePEc:zbw:arlabe:33
Keywords: 710; Demographic change; safeguarding public service provision; rural border areas; cross-border approaches and projects; cross-border cooperation; Greater Region